Which shows 60^2 − 40^2 being evaluated using the difference of squares method?


A. 60^2 − 40^2 = (3600 + 1600)(3600 − 1600) = 10,400,000

B. 60^2 − 40^2 = 3600 − 1600 = 2,000

C. 60^2 − 40^2 = (60 − 40)^2 = 20^2 = 400

D. 60^2 − 40^2 = (60 + 40)(60 − 40) = (100)(20) = 2,000

Respuesta :

kanest
The difference of squares method uses the following formula:

[tex]a^{2} - b^{2} = (a+b)(a-b)[/tex]

Answer A has the squares multiplied out, then put into the formula, which is incorrect.

Answer B does not use this formula, as the squares are multiplied out and solved without using this method.

Answer C subtracts in terms of the power, which is completely wrong.

The answer is D.

Answer:

D. 60^2 − 40^2 = (60 + 40)(60 − 40) = (100)(20) = 2,000

Step-by-step explanation: